2019
DOI: 10.1021/acsomega.8b01854
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Performance Bismuth Sulfide Nanobelts Humidity Sensor and Effect of Humid Environment on its Transport Properties

Abstract: Orthorhombic phase bismuth sulfide (Bi 2 S 3 ) nanobelts were prepared via  liquid–solid phase reaction method. Bi 2 S 3 nanobelts were observed to be preferentially oriented along the (101) plane. Direct band gap (2.95 eV) and characteristic wavelength (λ max = 342 nm) were extracted through UV–visible spectroscopy. Specific surface area (9.8 m 2 /g) and pore size (2.5–120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…87,88 Bismuth Sulfide (Bi 2 S 3 )-Based Gas Sensors Only a few reports are available on Bi 2 S 3 -based gas and humidity sensors. 42,52 Kan et al measured NO 2 gas response of Pb(NO 3 ) 2 ,NaNO 2 , NaNO 3 , Zn(NO 3 ) 2 (as long-chain ligand exchanger)-treated Bi 2 S 3 films at room temperature. 42 They found that Pb(NO 3 ) 2 treatment generated more porous Bi 2 O 3 film that showed maximum response (58.8) as compared to other inorganic salt treatment.…”
Section: Bismuth Oxide (Bi 2 O 3 )-Based Gas Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…87,88 Bismuth Sulfide (Bi 2 S 3 )-Based Gas Sensors Only a few reports are available on Bi 2 S 3 -based gas and humidity sensors. 42,52 Kan et al measured NO 2 gas response of Pb(NO 3 ) 2 ,NaNO 2 , NaNO 3 , Zn(NO 3 ) 2 (as long-chain ligand exchanger)-treated Bi 2 S 3 films at room temperature. 42 They found that Pb(NO 3 ) 2 treatment generated more porous Bi 2 O 3 film that showed maximum response (58.8) as compared to other inorganic salt treatment.…”
Section: Bismuth Oxide (Bi 2 O 3 )-Based Gas Sensormentioning
confidence: 99%
“…42 Orthorhombic Bi 2 S 3 nanobelts were generated using a facile liquid-solid phase reaction technique by mixing a stoichiometric ratio of bismuth acetate (as a Bi source) and thiourea (as a sulphur). 52 Relatively low-temperature combustion (at 190°C) caused generation of very thin and porous nanobelts (pore size of 2.5-120 nm). The humidity sensor fabricated…”
Section: Bismuth Oxide (Bi 2 O 3 )-Based Gas Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…近年来, 湿度传感器已 在呼吸速率检测、非接触式开关、皮肤湿度检测、婴 儿尿布润湿监测等方面获得实际应用. 目前, 石墨 烯 [98] 、硫化物 [99] 、金属氧化物 [100] 及其复合物 [101] 等材 料已被用作湿度传感器的活性材料. [45] .…”
Section: 传感unclassified
“…Solar energy has been regarded as the most potential clean and environment-friendly energy source to tackle the increasingly serious energy shortage and environmental pollution. , Developing functional materials for achieving solar energy conversion has attracted much attention among researchers. In recent years, layered orthorhombic bismuth sulfide (Bi 2 S 3 ) has emerged as a kind of promising semiconductors candidate in photocatalysts, , photoelectrochemical (PEC) devices, , sensors, , photovoltaic devices, , thermoelectric devices, , electrochemical energy storage cells, , and photothermal therapy due to its excellent optical and electrical properties such as a relatively narrow band gap and a high absorption coefficient. Moreover, the nontoxic nature of Bi 2 S 3 endows more competitiveness in green development compared with other metal chalcogenides . In the past decades, numerous reports have been focused on investigating the synthesis and properties of Bi 2 S 3 nanoparticles. , From the point of view of practical application, nanoparticles have several drawbacks, such as low reusability and strong light diffusion.…”
Section: Introductionmentioning
confidence: 99%